Development of E-Comic Learning Media to Improve Students' Learning Outcomes at Class X - Lili Maratus Solichah; Iin Baroroh Ma'arif; Hidayatur Rohmah (APPLICATION: Applied science in Learning Research, 2025)
This study aims to (1) Determine the development of E-comic media on the subject of Aqidah Akhlaq for class X. (2) To determine the results of student learning on E-comic media on the subject of Aqidah Akhlak for class X. The method used in this study is the Research and Development (R&D) research method, which was developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation)  model. The resulting product is validated by media experts and material experts, to determine the feasibility of the learning media before being tested. The results of this study obtained a score of 92% in material validation and 91% in media validation, which means that this learning media is categorized as "very feasible" to be tested. Student learning outcomes are assessed using the assessment report result which produce a score of 90% anad student response result of 92% with the category "very interesting". Thus, the E-comic learning media in the subject of Aqidah Akhlak class X, is categorized as very feasible to be used in learning and students are very interested in using it